Annual variation and synodic modulation of the sporadic meteoroid flux to the Moon. Issue 24 (31st December 2015) - Szalay, Jamey R.; Horányi, Mihály
Abstract: The Lunar Dust Experiment on board NASA's Lunar Atmosphere and Dust Environment Explorer discovered a permanently present, asymmetric dust cloud engulfing the Moon, sustained by meteoroid bombardment. It is most dense at 5–8 lunar local time, with a peak density canted sunward. Here we present analysis on the variation of the cloud density during January to April 2014. We find the lunar dust cloud in the Moon's equatorial plane to be dominantly produced by impacts from three known sporadic meteoroid sources: apex, helion, and antihelion, listed in order of their contribution to ejecta production. The cloud density is also modulated by the Moon's orbital motion about the Earth, peaking during its waning gibbous phase. These results are complementary to ground‐based measurements and indicate the Moon can be used as a very sensitive large area dust detector to characterize the meteoroid environment at 1 AU. Key Points: The apex, helion, and antihelion sources are dominant sources of lunar ejecta The Moon's dust cloud is very sensitive to changes in meteoroid flux The Moon provides a complementary resource to characterize meteoroids at 1 AU